Diosgenyl 2-amino-2-deoxy-β-D-galactopyranoside: synthesis, derivatives and antimicrobial activity - Myszka, Henryk; Sokołowska, Patrycja; Cieślińska, Agnieszka; Nowacki, Andrzej; Jaśkiewicz, Maciej; Kamysz, Wojciech; Liberek, Beata (Beilstein Journal of Organic Chemistry, 2017)
The synthesis of diosgenyl 2-amino-2-deoxy-β-D-galactopyranoside is presented for the first time. This synthetic saponin was transformed into its hydrochloride as well as N-acyl, 2-ureido, N-alkyl, and N,N-dialkyl derivatives. Antifungal and antibacterial studies show that some of the obtained compounds are active against Gram-positive bacteria and Candida type fungi.
Keywords: antimicrobial activities; D-galactosamine; diosgenin; glycosylation; saponin; tetrachlorophthalimido derivatives

Saponins: properties, applications and health benefits - Chindo, B. A.; Adzu, B.; Gamaniel, K. S. (Saponins: structural diversity, properties and applications, 2012)

(untitled) - Sparg, S. G.; Light, M. E.; van Staden, J. (J. Ethnopharmacol., 2004)

(untitled) - Iorizzi, M.; Lanzotti, V.; Ranalli, G.; De Marino, S.; Zollo, F. (J. Agric. Food Chem., 2002)

(untitled) - Zhang, J.-D.; Cao, Y.-B.; Xu, Z.; Sun, H.-H.; An, M.-M.; Yan, L.; Chen, H.-S.; Gao, P.-H.; Wang, Y.; Jia, X.-M.; Jiang, Y.-Y. (Biol. Pharm. Bull., 2005)

(untitled) - Yang, C.-R.; Zhang, Y.; Jacob, M. R.; Khan, S. I.; Zhang, Y.-J.; Li, X.-C. (Antimicrob. Agents Chemother., 2006)

(untitled) - Chapagain, B. P.; Wiesman, Z.; Tsror (Lahkim), L. (Ind. Crops Prod., 2007)

(untitled) - Man, S.; Gao, W.; Zhang, Y.; Huang, L.; Liu, C. (Fitoterapia, 2010)

(untitled) - Pérez-Labrada, K.; Brouard, I.; Estévez, S.; Marrero, M. T.; Estévez, F.; Bermejo, J.; Rivera, D. G. (Bioorg. Med. Chem., 2012)

(untitled) - Liu, Z.; Gao, W.; Jing, S.; Zhang, Y.; Man, S.; Wang, Y.; Zhang, J.; Liu, C. (J. Ethnopharmacol., 2013)

(untitled) - Thakur, M.; Melzig, M. F.; Fuchs, H.; Weng, A. (Bot.: Targets Ther., 2011)

Advances in Plant Glycosides, Chemistry and Biology - Yang, C.-R.; Tanaka, O. (Elsevier, 1999)

(untitled) - Hou, S. J.; Zou, C. C.; Zhou, L.; Xu, P.; Yu, D. Q.; Lei, P. S. (Chin. Chem. Lett., 2007)

(untitled) - Wang, B.; Chun, J.; Liu, Y.; Han, L.; Wang, Y.-s.; Joo, E.-J.; Kim, Y.-S.; Cheng, M.-s. (Org. Biomol. Chem., 2012)

(untitled) - Bansal, R.; Acharya, P. C. (Chem. Rev., 2014)

(untitled) - Fang, M.; Gu, L.; Gu, G.; Fang, J. (J. Carbohydr. Chem., 2012)

(untitled) - Gu, G.; An, L.; Fang, M.; Guo, Z. (Carbohydr. Res., 2014)

(untitled) - Yang, S.-L.; Liu, X.-K.; Wu, H.; Wang, H.-B.; Qing, C. (Steroids, 2009)

(untitled) - Gao, J.; Li, X.; Gu, G.; Sun, B.; Cui, M.; Ji, M.; Lou, H.-X. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Zhang, Y.; Zhang, Y.-J.; Jacob, M. R.; Li, X.-C.; Yang, C.-R. (Phytochemistry, 2008)

(untitled) - Yu, B.; Zhang, Y.; Tang, P. (Eur. J. Org. Chem., 2007)

(untitled) - Zhao, Y.; An, L.; Gu, G.; Guo, Z. (J. Carbohydr. Chem., 2014)

(untitled) - Yang, Y.; Laval, S.; Yu, B. (Adv. Carbohydr. Chem. Biochem., 2014)

(untitled) - Bednarczyk, D.; Kaca, W.; Myszka, H.; Serwecińska, L.; Smiatacz, Z.; Zaborowski, A. (Carbohydr. Res., 2000)

(untitled) - Myszka, H.; Bednarczyk, D.; Najder, M.; Kaca, W. (Carbohydr. Res., 2003)

(untitled) - Kaskiw, M. J.; Tassotto, M. L.; Th’ng, J.; Jiang, Z.-H. (Bioorg. Med. Chem., 2008)

(untitled) - Kaskiw, M. J.; Tassotto, M. L.; Mok, M.; Tokar, S. L.; Pycko, R.; Th’ng, J.; Jiang, Z.-H. (Bioorg. Med. Chem., 2009)

(untitled) - Cirioni, O.; Myszka, H.; Dawgul, M.; Ghiselli, R.; Orlando, F.; Silvestri, C.; Brescini, L.; Kamysz, W.; Guerrieri, M.; Giacometti, A. (J. Med. Microbiol., 2011)

(untitled) - Wang, B.; Liu, Y.; Wang, Y.; Liu, X.; Cheng, M.-S. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Fernández-Herrera, M. A.; López-Muñoz, H.; Hernández-Vázquez, J. M. V.; Sánchez-Sánchez, L.; Escobar-Sánchez, M. L.; Pinto, B. M.; Sandoval-Ramírez, J. (Eur. J. Med. Chem., 2012)

(untitled) - Bednarczyk, D.; Walczewska, A.; Grzywacz, D.; Sikorski, A.; Liberek, B.; Myszka, H. (Carbohydr. Res., 2013)

(untitled) - Walczewska, A.; Grzywacz, D.; Bednarczyk, D.; Dawgul, M.; Nowacki, A.; Kamysz, W.; Liberek, B.; Myszka, H. (Beilstein J. Org. Chem., 2015)

(untitled) - Jiménez Blanco, J. L.; Ortega-Caballero, F.; Ortiz Mellet, C.; Garcia Fernández, J. M. (Beilstein J. Org. Chem., 2010)

(untitled) - McKay, M. J.; Nguyen, H. M. (Carbohydr. Res., 2014)

(untitled) - Cai, J.; Davison, B. E.; Gianellin, C. R.; Thaisrivongs, S.; Wibley, K. S. (Carbohydr. Res., 1997)

(untitled) - Liberek, B.; Melcer, A.; Osuch, A.; Wakieć, R.; Milewski, S.; Wiśniewski, A. (Carbohydr. Res., 2005)